PENGARUH PANJANG PIPA KATALIS HYDROCARBON CRACK SYSTEM TERHADAP EMISI GAS BUANG : EFFECT OF HYDROCARBON CRACK SYSTEM CATALYST PIPE LENGTH ON EXHAUST GAS EMISSIONS - Ahmed Sabili Gifari; Ahmad Hanif Firdaus (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
Exhaust emissions are pollutants that pollute the air caused by exhaust gases from motor vehicles. The purpose of this study is to determine the results of the effect of catalyst pipe length on the Hydrocarbon Crack System on exhaust emissions of four-cylinder gasoline motorcycles. The research method uses experimental method to analyze the Hydrocarbon Crack System tool. The results showed that variations in catalyst pipe length had an effect on reducing exhaust emissions. The test results showed the highest HC reduction of 29.7% in the 200mm catalyst length variation at 2000rpm rotation, and the highest CO reduction of 4.3% in the 20mm catalyst pipe length variation at 3000rpm rotation